2009
DOI: 10.1021/bk-2009-1018.ch009
|View full text |Cite
|
Sign up to set email alerts
|

Fate and bioavailability of sulfamethazine in freshwater ecosystems

Abstract: The antibiotic sulfamethazine can be transported from manured fields to surface water bodies. We investigated the degradation, fate, and bioavailability of sulfamethazine in surface water using 14C-U-phenylsulfamethazine in small pond water microcosms. Sulfamethazine dissipated exponentially from the water column, with the majority of loss occurring via movement into the sediment phase. Manure input significantly increased sorption and binding of sulfamethazine residues to the sediment. These results indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Our results and those of others (9,34,36,37) show that erythromycin and other antibiotics partition from the overlying water into stream and pond sediments. We examined the dissipation of erythromycin residues in sediment that had been previously aged for 1, 3 or 8 weeks.…”
Section: Aged Residues Study: Sedimentsupporting
confidence: 85%
“…Our results and those of others (9,34,36,37) show that erythromycin and other antibiotics partition from the overlying water into stream and pond sediments. We examined the dissipation of erythromycin residues in sediment that had been previously aged for 1, 3 or 8 weeks.…”
Section: Aged Residues Study: Sedimentsupporting
confidence: 85%
“…Treatment preparation was briefly described by Henderson et al (2009). 22 The fate of sulfamethazine was examined in four pond water systems: pond water and sediment (PWS), autoclaved pond water and sediment, pond water without sediment (PW), and pond water and sediment with SMZ added with dilute manure (PWS +M) with four replications of each. Microcosms were constructed by adding 73 g of sediment (50 g dry wt) into wide-mouth pint jars (Ball Corp., Broomfield, CO), and topped with 177 mL of pond water to equal 200 mL of water per jar.…”
Section: ■ Experimental Materials and Methodsmentioning
confidence: 99%
“…Thus, the hydrolysis of these antibiotics is not to be expected in surface water, groundwater or anaerobic lagoons. The recent study of Henderson et al (2009) has confirmed that in respect to the bioconcentration factor, sulfamethazine belongs to the class of persistent hydrophobic contaminants. Thus, sediment is a potential sink for this contaminant.…”
Section: Photodegradationmentioning
confidence: 86%